THE CLINICAL POLYMORPHISM AND TREATMENT STRATEGY IN A LARGE FAMILY WITH BRUGADA SYNDROME - S. Saber; A. F. Fazelifar; M. Haghjoo; Z. Emkanjoo; A. Alizadeh; M. Shojaifard; M. Dalili; M. Houshmand; A. V. Gavrilenko; E. V. Zaklyazminskaya (Российский кардиологический журнал)
Brugada syndrome (BrS) is an inherited arrhythmia characterized by ST-segment elevation in V1-V2 leads followed by negative T-wave on standard ECG, and high risk of ventricular tachyarrhythmias and sudden cardiac death (SCD). A wide range of supraventricular arrhythmias and conduction disturbances was described for BrS. The disease was considered of the high frequency in Southeast Asia, but current estimation of BrS is at least 1:10 000 in all ethnic groups. At least 17 genes are known to be responsible for BrS. Approximately 15-30% of individuals with Brugada syndrome cases are affected by mutations in SCN5A gene. In this study we discuss the clinical polymorphism and surgical treatment in a large family with Brugada syndrome caused by p.A735V mutation in SCN5A gene.